2020
DOI: 10.1002/gcc.22886
|View full text |Cite
|
Sign up to set email alerts
|

Detection of tetraploidization in chromophobe renal cell carcinoma: Insights and pitfalls

Abstract: Chromosomal losses resulting in a marked hypodiploidy are a specificity of chromophobe renal cell carcinoma (ChRCC), the third most frequent type of kidney cancer. Its detection is useful in challenging cases. However some ChRCC, especially the eosinophilic variant, do not exhibit hypodiploidy and deserve to be better explored. Using comparative genomic hybridization (array-CGH) we observed chromosomal gains in five cases of nonmetastatic ChRCC. Our objective was to determine whether these apparent chromosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…In addition to VEGF, Ang is also closely associated with angiogenesis, and Ang-1 and Ang-2 in this protein family belong to angiogenesis regulators. Numerous studies have confirmed that their expression levels are closely related to tumor stages and patient prognosis [ 15 , 16 ]. Therefore, Ang, VEGF, and CRP were selected as the serological indicators to explore the value of their combined detection for patients with advanced renal cancer after treating with the Chinese medicine antitumor formula.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to VEGF, Ang is also closely associated with angiogenesis, and Ang-1 and Ang-2 in this protein family belong to angiogenesis regulators. Numerous studies have confirmed that their expression levels are closely related to tumor stages and patient prognosis [ 15 , 16 ]. Therefore, Ang, VEGF, and CRP were selected as the serological indicators to explore the value of their combined detection for patients with advanced renal cancer after treating with the Chinese medicine antitumor formula.…”
Section: Introductionmentioning
confidence: 99%